2017
DOI: 10.1177/0265407517740640
|View full text |Cite
|
Sign up to set email alerts
|

Young adults’ sibling relationships: Italian adaptation and validation of the Lifespan Sibling Relationship Scale

Abstract: To deepen our understanding of young adults’ sibling relationships in the Italian context, this study examines the psychometric properties of the Italian adaptation and validation of the Lifespan Sibling Relationship Scale (LSRS) in a sample of 350 Italian university students (68.6% females, 31.4% males; ages 19–30 year, M = 23.6, SD = 3.2). Confirmatory factor analysis showed the expected six-factor structure and a close correlation between factors and scales. Internal consistency was adequate and correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
4
13
0
Order By: Relevance
“…In the current study, female emerging adults also reported significantly higher scores than Turkish male emerging adults in Adult subscales, suggesting that female participants have closer and more satisfying relations with their siblings than male participants do. This finding is in line with the results of Riggio (2000) and Sommantico et al (2017). The current study also revealed that female participants reported significantly higher scores than male participants, particularly on Adult Affect and Adult Behavior subscales.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, female emerging adults also reported significantly higher scores than Turkish male emerging adults in Adult subscales, suggesting that female participants have closer and more satisfying relations with their siblings than male participants do. This finding is in line with the results of Riggio (2000) and Sommantico et al (2017). The current study also revealed that female participants reported significantly higher scores than male participants, particularly on Adult Affect and Adult Behavior subscales.…”
Section: Discussionsupporting
confidence: 92%
“…The result indicated that the measurement model is invariant and the construct identities are the same across the genders. In addition, the reliability of test scores for all subscales and total score revealed good internal consistency reliability, which is consistent with previous studies (Jeong et al, 2013;Riggio, 2000;Sommantico et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Dialogue on the illness within the family allows an opportunity to share medical information as well as to address many other issues: collecting information on the disease, providing a space for the child to share about the disease from an emotional perspective, and about talking about it with significant others. Within this domain, it is possible to observe how the various dialogical modalities of sharing information and knowledge between caregivers and children, and even brothers and sisters, can respond to specific functions (Sommantico et al, 2017). Each caregiver and family differs in terms of dialogical styles as well as for a greater or lesser ability to accompany their child in the construction of meaning of the path of illness (Clarke et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The LSRS is a 48-item self-report instrument (Riggio, 2000; Italian adaptation and validation: Sommantico, Donizzetti, De Rosa, & Parrello, 2017) which assesses the feelings, behaviors, and thoughts related to sibling relationships in childhood and adulthood on six subscales: (1) Adult Affect (Items 1-8; Item 6 “reverse keyed”), (2) Adult Behavior (Items 9-16; Item 13 “reverse keyed”), (3) Adult Cognition (Items 17-24; Item 19 “reverse keyed”), (4) Child Affect (Items 25-32; Items 25, 27, and 28 “reverse keyed”), (5) Child Behavior (Items 33-40; Item 38 “reverse keyed”), and (6) Child Cognition (Items 41-48; Item 42 “reverse keyed”). The affective component is operationalized by assessing emotions toward the sibling and the sibling relationship (e.g., “My sibling’s feelings are very important to me”).…”
Section: Methodsmentioning
confidence: 99%